Artificial intelligence and learning process management in secondary school students. Educational institution N° 6019 Mariano Melgar. Lima - Caballero Meza , Diana Vanessa (2025)
The purpose of this study is to examine how Artificial Intelligence impacts students' educational process. The methodology adopted is basic; the level is descriptive-correlational; the hypothesis is tested using a deductive method; the design is non-experimental and descriptive in nature; the sample consisted of 40 students; simple random sampling was used, collecting data through surveys and a questionnaire, and the data was analyzed using the statistical software SPSS27. The result was a score (0.646) between the main variable, Artificial Intelligence, and the educational process. The recommendation is the gradual inclusion of Artificial Intelligence in educational activities and the training of teachers in the use of this technological innovation.